Analisis Dampak Audit Tenure, Rotasi Audit, Dan Fee Audit Terhadap Kualitas Audit - Linda Agustina Saputri; Cris Kuntadi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The purpose of the research is to investigate how audit tenure, audit rotation and audit fees influence audit quality. This research uses qualitative literature study methods as the basis for its methodology. The results of the research obtained that the use of all variables had a positive influence, namely audit tenure, audit rotation and audit fees had a positive and significant influence on audit quality.